The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1371/journal.pone.0017457
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Depression with Ischemic Heart Disease: A Population-Based Longitudinal Study Comparing Interventional Approaches to Medical Management

Abstract: BackgroundWe compared the proportion of ischemic heart disease (IHD) patients newly diagnosed with dementia and depression across three treatment groups: percutaneous coronary intervention (PCI), coronary artery bypass grafting (CABG) and medical management alone (IHD-medical).Methods and FindingsDe-identified, individual-level administrative records of health service use for the population of Manitoba, Canada (approximately 1.1 million) were examined. From April 1, 1993 to March 31, 1998, patients were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…We also included 2 further cohort studies16,17 comparing the risk of all-cause dementia and AD in those with CABG to those with PCI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also included 2 further cohort studies16,17 comparing the risk of all-cause dementia and AD in those with CABG to those with PCI.…”
Section: Resultsmentioning
confidence: 99%
“…Our meta-analytic results suggest the significant association between history of CABG and dementia risk is unlikely to be driven by the underlying CAD as PCI may be associated with lower dementia risk compared with CABG. One study investigated dementia risk in those with a history of CABG compared with those receiving medical management for CAD and found no significant association, though this was limited by the use of medical records for the primary outcome 16. Further well-designed studies are needed to compare CABG with alternative treatment strategies for CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, a much larger subsequent Canadian population-based longitudinal study did not replicate this finding. 93 Several population epidemiological studies have recently been published, yielding conflicting and provocative results. Two Taiwanese studies drawn from national databases 94 95 and a large French population study 96 have all found a link between surgery or anaesthesia and subsequent incident dementia.…”
Section: Non-modifiable Factors: Age Genes and Dementiamentioning
confidence: 99%
“…First, the apolipoprotein E genotype associated with dementia is reportedly unrelated to POCD incidence in patients undergoing CABG surgery. 88 Second, a recent epidemiological study in Canada 89 reported that the proportion of patients with ischemic heart disease who subsequently received a diagnosis of dementia during 3 to 8 years of follow-up was 7.0% for those who were treated with CABG surgery and 12.1% for those who received conservative medical management only; this difference was not statistically significant.…”
Section: Preoperative Cognitive Variability -Chronic Influences On Brmentioning
confidence: 97%